A study on the validity and applicability of microplate phage replication assay (MPRA) for rifampicin sensitivity testing of some mycobacterium tuberculosis isolates in the Philippines - Olobia, Leonido P. (2001)
A study on the Microplate Phage Replication Assay (MPRA), a bacteriophage-based drug sensitivity test was undertaken to determine its applicability and validity in the local setting.The study used the drug rifampicin and some Mycobacterium tuberculosis isolates obtained from pulmonary tuberculosis patients in the Philippines, using Modified Proportion Method (Submerged Disc Method) as the gold standard. MPRA is based on the principle that viable TB bacilli (i.e., drug-resistant) protect infecting mycobacteriophage from chemical inactivation and support the replication of the infecting phages.Eighty-two isolates (82) of M. tuberculosis from the TB Research Laboratory of the Bureau of Research and Laboratories, Department of Health and the Department of Medical Microbiology, College of Public Health, University of the Philippines Manila were tested. Of the 82 M. tuberculosis isolates examined by Proportion Method, 34 (41) were rifampicin-resistant and 48 (59) were rifampicin-sensitive. The MPRA results were different from the previous studies done abroad (McNerney et al., 1998: McNerney et al., 2000).The probable factors that could account for the difference in the results are: first, the phage used in the study could have been replaced by another phage specifically L5, which only infects M. smegmatis. The ubiquitous phage L5 could have come from contamination of the original phage D29 during its 8 months of storage in the refrigerator, transport from London to the Philippines, or probably due to mislabelling in the London laboratory. Second, the slow rate of growth of BCG M. tuberculosis probably resulted in the lack of host cells available for the phage since these mycobacteria were exposed only for 24 hours in Luria broth with supplements prior to phage infection. The lack of host cells available to the phage could have been due also to the clumps of mycobacterial cells that were not completely dispersed because of the hydrophobic nature of mycobacteria. Third, the phage concentration used in the MPRA could have resulted in high phage-to cell-ratio causing the "killing from without" phenomenon where cells in the area were lysed but no progeny viruses were produced (Sarkis and Hatfull, 1993; Pelczar et al., 1993). Lastly, the MPRA procedures are not yet fully standardized/optimized including the preparation of the mycobacterial inocula and the working phage solution.It is also recommended that future studies for MPRA should make use of new reference strains of M. smegmatis, BCG and mycobacteriophage D29 from an accredited culture collection institution.